Associations between Education, Knowledge, Attitude, and Maternal Intention on Antenatal Care Visit - Panjaitan, Polma Ria Metawati; Santosa, Heru; Utama, Surya (Journal of Maternal and Child Health, 2019)
Background: Good quality of health care is important for maternal and infants health. Regular antenatal visit can assist in identifying and reducing risks of mother and infant during pregnancy. This study aimed to examine the associations between education, knowledge, attitude, and maternal intention on antenatal care (ANC) visit.Subjects and Method: A cross sectional study was carried out at Ridos hospital, Medan, North Sumatera, in 2017. A sample of 89 pregnant women was selected by accidental sampling. The dependent variable was ANC visit. The independent variables were education, knowledge, and attitude. The data were collected by questionnaire and analyzed by linear multiple regression.Results: Maternal intention to do ANC visit increased with high education (b= 0.36; p= 0.001), knowledge (b= 0.48; p= 0.001), and attitude (b = 0.24; p= 0.001).Conclusion: Maternal intention to do ANC visit increased with high education, knowledge, and attitude.Keywords: antenatal care, pregnant womenCorrespondence: Polma Ria Metawati Panjaitan. Masters Program in Public Health, Universitas Sumatera Utara. Jl. Universitas 21, Medan 20155, North Sumatera. Email: happypolma@yahoo.com. Mobile: 081370801033.Journal of Maternal and Child Health (2019), 4(6): 516-521https://doi.org/10.26911/thejmch.2019.04.06.12